Exosomal-microRNA transcriptome profiling of parental and CSC-like MDA-MB-231 cells in response to cisplatin treatment - Koh, May Zie; Ho, Wan Yong; Yeap, Swee Keong; Mohd Ali, Norlaily; Yong, Chean Yeah; Boo, Lily; Alitheen, Noorjahan Banu (Elsevier, 2022)
Triple negative breast cancer (TNBC) is the most aggressive breast cancer subtype with higher risk of metastasis and cancer reoccurrence. Cisplatin is one of the potential anticancer drugs for treating TNBC, where its effectiveness remains challenged by frequent occurrence of cisplatin resistance. Since acquirement of drug resistance often being associated with presence of cancer stem cells (CSCs), investigation has been conducted, suggesting CSC-like subpopulation to be more resistant to cisplatin than their parental counterpart. On the other hand, plethora evidences showed the transmission of exosomal-miRNAs are capable of promoting drug resistance in breast cancers. In this study, we aim to elucidate the differential expression of exosomal-microRNAs profile and reveal the potential target genes in correlation to cisplatin resistance associated with CSC-like subpopulation by using TNBC cell line (MDA-MB-231). Utilizing next generation sequencing and Nanostring techniques, cisplatin-induced dysregulation of exosomal-miRNAs were evaluated in maximal for CSC-like subpopulation as compared to parental cells. Intriguingly, more oncogenic exosomal-miRNAs profile was detected from treated CSC-like subpopulation, which may correlate to enhancement of drug resistance and maintenance of CSCs. In treated CSC-like subpopulation, unique clusters of exosomal-miRNAs namely miR-221–3p, miR-196a-5p, miR-17–5p and miR-126–3p were predicted to target on six genes (ATXN1, LATS1, GSK3β, ITGA6, JAG1 and MYC), aligned with previous finding which demonstrated dysregulation of these genes in treated CSC-like subpopulation. Our results highlight the potential correlation of exosomal-miRNAs and their target genes as well as novel perspectives of the corresponding pathways that may be essential to contribute to the attenuated cytotoxicity of cisplatin in CSC-like subpopulation.